PROFIL KARAKTERISTIK DAN KOMPETENSI GURU BIOLOGI SMA NEGERI 1 BAJODI ERA REVOLUSI INDUSTRI 4.0 - Irwani Irwani; Irwanto Irwanto (Universitas Sultan Ageng Tirtayasa, 2019)
ABSTRACTTeacher problems are increasingly complex entering the industrial era 4.0, where teachers must have competence in facing technological developments. This study aims to determine the characteristics and competencies of biology teachers in the delivery of material to students in the classroom and outside the classroom in the current era of industrial revolution. The method used in this study is a qualitative method with a descriptive approach. The population in this study were all biology teachers in SMA 1 Bajo South Sulawesi in the 2018/2019 school year. The sample in this study were teachers who taught biology subjects in SMA 1 Bajo, totaling 6 teachers. Data collection techniques use observation sheets directly into the classroom or outside the classroom, teacher competency questionnaires that must be filled in by the teacher. Based on the results of the study indicate that, the characteristic profile and competency of biology teachers in SMA 1 Bajo can be said to meet the standards in the assessment of a biology teacher. But in this study examines efforts in increasing biology teacher competence towards the era of industrial revolution 4.0. in an effort to improve the competence of biology teachers by improving the system of teacher recruitment, the pattern of increasing teacher competency that is bottom up, empowering groups of teacher activities and discussion of biology subject teachers to create a collaboration that is oriented to the development of a teacher and optimization of sustainable professional improvement programs and lesson study with e-literacy support. The achievement of the competence of biology teachers in 1 Bajo Public High School is 70% pedagogical competence, 80% achievement personality competency, 90% achievement of social competence, and 75% professional competence achievement. Keywords: characteristics, competence, biology teacher, industrial revolution 4.0.